DIGITAL MARKETING COMMUNICATION TO INCREASE CRSL STORE BRAND AWARENESS - Salim, Mufid; Rosdian, Erwin Dwi Sabna; Marta, Rustono Farady (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
CRSL Store is a clothing store or distribution company that produces various bags, backpacks, garments, jackets, headgear, and footwear. The CRSL brand attracted many people because of its unique products, which consisted of five adorable animal figures. CRSL indirectly undertakes a "save animal" campaign through the products it makes. Strong CRSL brand identity must be continually maintained and strengthened to build brand awareness. Digital marketing communications is one of the tactics employed by CRSL to raise brand recognition. This research determines how much CRSL uses digital marketing to boost brand recognition. The researcher method used in this research is descriptive qualitative, with the CRSL brand as the subject of investigation. Interview, observation, and documentation approaches were utilized to obtain data, while three stages of data analysis are used, including data reduction, display, and verification. Furthermore, the triangulation method was used to assess the data's veracity. Seven sources were consulted, including CRSL's CEO, Chief in Editor, Store Manager, COO, and three CRSL customers. The results reveal that CRSL has increased brand awareness by incorporating components of digital marketing communications. These elements include websites, social media marketing, search engine marketing, email marketing, video marketing, and online advertising. Several of these features, such as search engine marketing and email marketing, are still in the early stages of development. The digital marketing plan carried out by CRSL is supported by segmentation, targeting, and positioning techniques to group a large market. The number of Instagram followers, viewers on TikTok social media, and website visitors have increased, indicating that CRSL's brand recognition has grown. It may continue to raise CRSL brand recognition with a strong brand identity and a brilliant digital marketing communications strategy.